The deadly sister - Schrefer, Eliot (Scholastic Press, 2010)
Abby Goodwin has always covered for her sister, Maya. but now Maya has been accused of murder, and Abby's not sure she'll be able to cover for her sister anymore. Abby helps Maya escape. But when Abby begins investigating the death, she find that you can't trust anyone, not even the people you think you know.